Why human rights matter for marine conservation - Smallhorn-West, Patrick; Allison, Edward (Eddie); Gurney, Georgina; Karnad, Divya; Kretser, Heidi; Lobo, Aaron; Mangubhai, Sangeeta; Newing, Helen; Pennell, Kamille; Raj, Sushil; Tilley, Alexander; Williams, Haley; et al. (Frontiers Media, 2024)
Human rights matter for marine conservation because people and nature are inextricably linked. A thriving planet cannot be one that contains widespread human suffering or stifles human potential; and a thriving humanity cannot exist on a dying planet. While the field of marine conservation is increasingly considering human well-being, it retains a legacy in some places of protectionism, colonialism, and fortress conservation. Here, we i) provide an overview of human rights principles and how they relate to marine conservation, ii) document cases where tensions have occurred between marine conservation goals and human rights, iii) review the legal and ethical obligations, and practical benefits, for marine conservation to support human rights, and iv) provide practical guidance on integrating human rights principles into marine conservation. We argue that adopting a human rights-based approach to marine conservation, that is integrating equity as a rights-based condition rather than a charitable principle, will not only help meet legal and ethical obligations to respect, protect, and fulfil human rights, but will also result in greater and more enduring conservation impact.